INCREASING STUDENT INTERESTS THROUGH THE PJBL MODEL FOR LEARNING MATHEMATICS IN THE MATERIAL OF CUBE NETS IN GRADE 5 SDN 8 WANAREJAN - Trimurtini; Bernika Irnadialis Pramudita; Anika May Wulandari; Fitra Khasanatus Sholihah (Yayasan Thaifah Manshurah Pekanbaru, 2022)
One way that can be done to make learning fun and not boring is to apply a variety of learning models. Teachers need to choose a learning model that fits the material, fits the characteristics of the students, and uses projects/activities as media. The learning model in question is the Project Based Learning or project-based learning. In this study, researchers used a classroom action research method. In the core activities students explain how they will carry out learning activities. Begin to be introduced by dividing the group into 3 groups with 5-6 students as members. Then they were explained about class roaming so they explored each existing post. In this study there are 5 posts that are in accordance with the project based learning (PjBL) syntax. Based on the results of the research that has been carried out, it shows that learning using the learning model (PjBL) gets a good response from students. This is evidenced by the students' answers to the response questionnaire given. Most of the students, namely 86%, chose to strongly agree to the response questionnaire given. Results of students' responses to grade 5 learning with KD 3.7 Explaining and finding simple geometric nets (cubes and blocks), 4.6 Making simple geometric nets (cubes and blocks)